2024
DOI: 10.1038/s41557-023-01431-7
|View full text |Cite
|
Sign up to set email alerts
|

Bistability between π-diradical open-shell and closed-shell states in indeno[1,2-a]fluorene

Shantanu Mishra,
Manuel Vilas-Varela,
Leonard-Alexander Lieske
et al.

Abstract: Indenofluorenes are non-benzenoid conjugated hydrocarbons that have received great interest owing to their unusual electronic structure and potential applications in nonlinear optics and photovoltaics. Here we report the generation of unsubstituted indeno[1,2-a]fluorene on various surfaces by the cleavage of two C–H bonds in 7,12-dihydroindeno[1,2-a]fluorene through voltage pulses applied by the tip of a combined scanning tunnelling microscope and atomic force microscope. On bilayer NaCl on Au(111), indeno[1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We generated a nonbenzenoid polycyclic conjugated hydro- 47 or molecular conformation, 48 through proximity to adsorbates, 49 or by means of external fields. 50…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated a nonbenzenoid polycyclic conjugated hydro- 47 or molecular conformation, 48 through proximity to adsorbates, 49 or by means of external fields. 50…”
Section: Discussionmentioning
confidence: 99%
“…Electronic characterization of 1 by STM-based orbital-density imaging reveals an open-shell biradical ground state, with manifestation of the unusual phenomenon of SHI, wherein the SOMOs are lower in energy than the HOMO, which is in contrast to the majority of reported open-shell molecules. The demonstrated ability to detect SHI at the single-molecule level facilitates future experiments and applications of inducing or switching (on and off) SHI by changes in the adsorption site 47 or molecular conformation, 48 through proximity to adsorbates, 49 or by means of external fields. 50 …”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Among such CPHs conjugated indenofluorenes (IFs) possess one of the most interesting topologies of delocalized -electrons with different types of behavior (aromatic/antiaromatic) and ground state electronic structure (biradical/quinoidal). [16,17] They exhibit a 6-5-6-5-6 ring architecture, which is obtained by a fusion of the indene unit to various positions of the fluorene unit. Since 2010 all five possible IF regioisomers have been intensively studied by Haley's [18][19][20] and Tobe's [21,22] group (Structures 1-5 in, Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…25 Similarly, switching between the open-and closed-shell states of an indacene core has recently been observed by changing the adsorption site of an on-surface synthesized unsubstituted indeno[1,2-a]fluorene. 26 Alternatively, antiaromatic (IF) motifs can be generated by oxidation or reduction of more stable and readily accessible aromatic precursors, and is, in principle reversible. 27−34 However, this almost always proceeds via intermediate radical states that are typically unstable, potentially leading to undesired side reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Modulation of various molecular properties, including, in principle, (anti)­aromaticity can be achieved using molecular switches driven by various stimuli. For example, it was shown that photoswitching of a biphenylene-diarylethene allows to induce significant and reversible changes in the antiaromatic character of the central biphenylene motif by modulation of the conjugation pattern . Similarly, switching between the open- and closed-shell states of an indacene core has recently been observed by changing the adsorption site of an on-surface synthesized unsubstituted indeno­[1,2- a ]­fluorene …”
Section: Introductionmentioning
confidence: 99%